Research of bi‐directional DC/DC converter topology based on supercapacitor energy storage system in IP transmitter. Issue 16 (7th December 2018) - Zeng, Zhihui; Wang, Xiaowei; Wei, Yanfang; Yu, Yangxiao
Abstract : According to the energy storage requirement of IP transmitter in geophysical exploration, the practical application of the supercapacitor energy storage system in the polarisation instrument is proposed. In order to meet the requirement of the precise adjustment of the output voltage of the supercapacitor energy storage system in the storage process of the polarisation instrument and the change range of the terminal voltage wide during the charging and discharging process of the supercapacitor group and pursue the high efficiency, high power density, and high reliability of the energy storage system, a novel‐cascaded bidirectional Buck/Boost‐LLC DC‐DC converter topology is proposed and the system efficiency is analysed comparatively through the thermal simulation of the main switch device and the theoretical calculation of loss. Results show that the topology structure can achieve soft switching in the full load range, greatly reduce the power converter in the switching losses, improve the efficiency and power density of the energy storage system with its novel structure. The practical application of the supercapacitor energy storage system based on IP transmitter is studied and the results show the feasibility and superiority of the topology.